Sindrom Delirium - Andy Luman (Cermin Dunia Kedokteran, 2015)
Delirium merupakan suatu kondisi akut penurunan perhatian, kognitif, dan berfluktuasi yang sering dijumpai pada individu berusia 65 tahun atau lebih, biasanya disebabkan oleh suatu kondisi medis atau obat. Pemahaman gambaran klinis sangat diperlukan untuk diagnosis delirium secara bedside; dan dengan strategi pencegahan dan penanganan yang baik maka prognosisnya baik.Delirium is an acute condition of decreased and fluctuating attention and cognition, often found in individuals aged above 65 years, can be caused by a medical condition or drug adverse effect. Clinical understanding is very necessary for the diagnosis of delirium in bedside; and understandings of clinical symptoms are needed. Prognosis is good after appropriate prevention and treatment strategies.